Study about labor and/or academic insertion of graduates with postgraduate degrees from the Faculty of psychology of the National University of Rosario (Argentina) - Martina Elizalde; Nadia Peralta (Educación, 2018)
This article describes the results of the research about the assessment and the academic and/or labor insertion of graduates with postgraduate degrees from the Facultad de Psicología (Faculty of Psychology) of the Universidad Nacional de Rosario (National University of Rosario), Argentina. A descriptive analysis of data records from the academic unit has been carried out and results of surveys answered by graduates have also been analyzed. The results show that graduates have a positive assessment of the postgraduate courses, especially of the teacher role, the contents and their effects on academic training. They highlight aspects to be improved related to the teaching of methodology and thesis writing.